Microsimulation-based passenger car equivalents for heavy vehicles driving turbo-roundabouts - Giuffrè, Orazio; Granà, Anna; Marino, Sergio; Galatioto, Fabio (Transport, 2016)
Due to its geometric design, turbo-roundabouts impose greatest constraints to the vehicular trajectories; by consequence, one can expect a more unfavourable impact of heavy vehicles on the traffic conditions than on other types of roundabouts. The present paper addresses the question of how to estimate Passenger Car Equivalents (PCEs) for heavy vehicles driving turbo-roundabouts. The microsimulation approach used revealed as a useful tool for evaluating the variation of quality of traffic in presence of mixed fleets (different percentages of heavy vehicles). Based on the output of multiple runs of several scenarios simulation, capacity functions for each entry lane of the turbo-roundabout were developed and variability of the PCEs for heavy vehicles were calculated by comparing results for a fleet of passenger cars only with those of the mixed fleet scenarios. Results show a dependence of PCEs for heavy vehicles on operational conditions, which characterise the turbo-roundabout. Assuming the values of PCEs for roundabouts provided by the 2010 Highway Capacity Manual (HCM), depending on entering manoeuvring underestimation and overestimation of the effect of heavy vehicles on the quality of traffic conditions have been found.